Coeducation in Serial and Cinematographic Formats: Bibliometric Analysis on Web of Science (1986-2023) - Simón Gil Tévar; Jose Javier Hueso Romero; Javier Gil Quintana; Eduardo García Blazquez (MDPI AG, 2024)
This study quantitatively examines the coeducation of television series and films between 1986 and 2023. This analysis has been facilitated by applying bibliometric analysis to scientific production using a relevant Web of Science (WoS) database. Analyses of 190 documents were conducted using quantitative and descriptive methods. These results present a multifaceted analysis of scientific production, evaluating historical development, the productivity of countries and institutions, authors' productivity, and sources' productivity. The study indicates that scientific production has grown exponentially in the last decade; this coincides with the emergence of video-on-demand platforms, multiscreen consumption, and equality policies. The conclusions must emphasize the significant role played by fiction series and film productions as socializing agents and their educational potential.